Optical-electronic correlation-extreme navigation system of small unmanned aerial vehicle - A. A. Sheinikov; V. A. Malkin; E. A. Smolensky; L. A. Ivanitsky (Системный анализ и прикладная информатика)
An optical-electronic correlation-extreme navigation system for an unmanned aerial vehicle has been developed. The proposed navigation system is characterized by the use of a small-sized and affordable digital camera and computer, which is critical for small military unmanned aerial vehicles. The developed algorithmic support for the system is distinguished by the use of algorithms for reconstructing a three-dimensional digital terrain model using optical digital images from an on-board digital camera, as well as algorithms for correlation processing of current and reference models, which ensures the possibility of accurate autonomous air navigation using view information. The requirements for the flight parameters of a small unmanned aerial vehicle with an optical-electronic correlation-extreme navigation system are substantiated. The values of the true speed of an unmanned aerial vehicle and the correction period of the on-board strapdown inertial navigation system are substantiated according to the data of the proposed optical-electronic correlation-extreme navigation system. The results of the developed optical-electronic correlation-extremal navigation system accuracy studies depending on the shooting parameters and the quality of the reference models are presented.